AIR SPACE CONTROL AND SOVEREIGNTY: THE BRAZILIAN MODEL - Flávio Neri Hadmann Jasper; André Figueiredo Nunes (Revista Tempo do Mundo, 2022)
This study aims to analyze the creation of the Integrated Air Defense and Air Traffic Control System (Sistema Integrado de Defesa Aérea e Controle de Tráfego Aéreo – Sisdacta), from its conception, evolution and current situation, as well as its insertion as a factor that has generated international cooperation in security, defense and environmental monitoring. The creation of an integrated system had the challenge of providing the information necessary to maintain national sovereignty in the Brazilian airspace, providing an air traffic management system with international quality and an air defense system (today aerospace) that would rival the existing systems in first world countries, with lower implementation and operation costs. The research also provided a brief history of the creation of the Integrated System for the Protection of the Amazon (Sistema de Proteção da Amazônia – Sipam), a system created within a strand linked to ecology and derived from the agenda of the conference held in Rio de Janeiro, Eco-92. In addition, the work also analyzes the Integrated System of Surveillance of the Amazon (Sistema Integrado de Vigilância da Amazônia – Sivam) that became the Fourth Integrated Center for Air Defense and Air Traffic Control (Quarto Centro Integrado de Defesa Aérea e Controle de Tráfego Aéreo – Cindacta IV) based in Manaus, Amazonas, and, allied to that, approaches the international dimension of both systems in relation to cooperation with Amazonian countries that are members of the Amazon Cooperation Treaty Organization (ACTO). The research also briefly addresses the importance of external financing linked to long-term objectives that made it possible to make a strategic project of this magnitude possible in Brazil.